2005
DOI: 10.1590/s1516-89132005000200006
|View full text |Cite
|
Sign up to set email alerts
|

Dietary models for inducing hypercholesterolemia in rats

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
53
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 9 publications
12
53
2
1
Order By: Relevance
“…In the present study, this diet increased the total cholesterol and LDL-cholesterol and reduced HDL-cholesterol. This was consistent with earlier reports (Gonçalves et al, 2006;Matos et al, 2005;Turbino-Ribeiro et al, 2003). The treatment with annatto extract in animals fed with the high-lipid diet lowered LDL-and total cholesterol and raised HDL-cholesterol, suggesting its hypocholesterolemic effect.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the present study, this diet increased the total cholesterol and LDL-cholesterol and reduced HDL-cholesterol. This was consistent with earlier reports (Gonçalves et al, 2006;Matos et al, 2005;Turbino-Ribeiro et al, 2003). The treatment with annatto extract in animals fed with the high-lipid diet lowered LDL-and total cholesterol and raised HDL-cholesterol, suggesting its hypocholesterolemic effect.…”
Section: Discussionsupporting
confidence: 94%
“…Total energy was 17.18 kJ/kg. The high-lipid diet was the same, except for soybean oil, 250; cornstarch, 546; cholesterol, 10, with total energy 20.57 kJ/g (Matos et al, 2005). After 60 days, animals were fasted overnight and killed by decapitation.…”
Section: Methodsmentioning
confidence: 99%
“…This indicates that the standard diet did not influence the blood pressure of the animals. These data are consistent with the findings of (Matos et al, 2005) who carried out a tail pressure measurement with plethysmography in rats that received different diets. However, our data showed a significant reduction in the blood pressure levels in animals that received hypercholesterolemic diet in addition of bixin.…”
Section: Discussionsupporting
confidence: 91%
“…Animal models have been used to investigate the relationship between disorders in cholesterol metabolism and blood pressure (Matos et al 2005). The present study showed that the dietary model used was able to promote hipercholesterolemia and that the treatment with extracts of annatto seeds and bixin was able to decrease the blood pressure of rats.…”
Section: Discussionmentioning
confidence: 99%
“…The resultant decrease in body weight compared to controls might also be due to a decline in feed intake because of the high fat content of the cholesterol given, which might have impaired the absorption of protein and other nutrients (17,18).…”
Section: Discussionmentioning
confidence: 99%